Mare nostrum: the political ethics of migration in the Mediterranean - Rainer Bauböck (Comparative Migration Studies, 2019)
Abstract In the political theory debate about open borders and the ethics of immigration control there has been little discussion of trade-offs and a lack of distinctions between admission claims. This paper argues that freedom of movement, global distributive justice and democratic self-government form a trilemma that makes pursuing all three goals through migration policies difficult. It argues also that there are distinct normative grounds for refugee protection, admission of economic migrants and reciprocity-based free movement. Refugees have claims to protection of their fundamental human rights. Economic migrants should be admitted if there is a triple benefit for the receiving country, the country of origin and for themselves. Free movement is based on agreements between states to promote international mobility for their own citizens. These three normative claims call for different policy responses. However, in the current migration across the Mediterranean flows and motives are often mixed and policies of closure by destination states are bound to contribute to such mixing. The paper concludes by suggesting that the European Union as a whole has special responsibilities towards its geographic neighbours that include duties to admit asylum seekers, displaced persons and economic migrants.